Calcaneal osteoid osteoma hidden by confusing symptoms in an 18-year-old basketball player: A case report. (December 2016) - Testa, Marco; Rondoni, Angie; Francini, Luca
Abstract: Background: Osteoid osteoma is a small common benign osteoblastic tumor. Osteoid osteomas of the foot only account for a small number of cases. The typical patient is usually male children and young adults within the third decade. Objectives: By this case report we aim to: 1) analyze the reasons for initial misdiagnosis due to misleading previous sporting injury, and potential mimickers; and, 2) discuss different conservative and surgical therapeutic options. Clinical features: In our case report we describe an osteoid osteoma of the calcaneus in a young adult, semi-professional basketball player. Intervention and outcomes: A non-successful symptomatic intervention of joint mobilization and the presence of a nocturnal pain responsive to acetylsalicylic acid lead to a diagnosis of osteoid osteoma. The patient was successfully treated by percutaneous CT-guided radiofrequency thermoablation. Conclusions: The case suggests that close collaboration between general practitioner and physical therapist could have led to more efficient management of this rare disease. Osteoid osteoma should be considered in differential diagnosis when chronic foot pain, in children or in young adults, does not improve with conservative treatment.